THE INFLUENCE OF PEOPLE’S BUSINESS CREDIT (KUR) BRI UNIT ON SMALL BUSINESSES IN THE SUB-DISTRICT OF TANETE RIAJA, BARRU REGENCY - Armansyah, Budi; Amriani, Wiwi (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2018 Meraja journal